Beginning EJB 3 Java EE 7 Edition - Wetherbee, Jonathan; Kodali, Raghu; Rathod, Chirag; Zadrozny, Peter (Apress : Imprint: Apress, 2013)
Develop powerful, standards-based, back-end business logic with Beginning EJB 3, Java EE 7 Edition. Led by an author team with 20 years of combined Enterprise JavaBeans experience, you'll learn how to use the new EJB 3.2 APIs. You'll gain the knowledge and skills you'll need to create the complex enterprise applications that run today's transactions and more. Targeted at Java and Java EE developers, with and without prior EJB experience, Beginning EJB 3 is packed with practical insights, strategy tips, and code examples. As each chapter unfolds, you'll not only explore a new area of the spec; you'll also see how you can apply it to your own applications through specific examples. Beginning EJB 3 will serve not only as a reference, but it will also function as a how-to guide and repository of practical examples to which you can refer as you build your own applications. It will help you harness the power of EJBs and take your Java EE 7 development to the next level.